Metabolomics combined with proteomics provides a novel interpretation of the compound differences among Chinese tea cultivars (Camellia sinensis var. sinensis) with different manufacturing suitabilities. (30th May 2022) - Chen, Dan; Sun, Zhen; Gao, Jianjian; Peng, Jiakun; Wang, Zhe; Zhao, Yanni; Lin, Zhi; Dai, Weidong
Highlights: A combined metabolomics and proteomics study on 23 Chinese tea cultivars. The manufacturing suitability of tea cultivar is related with both metabolites and proteins. Enhanced amino acids biosynthesis and decreased flavanols biosynthesis in the GT cultivars. Enhanced flavonoids biosynthesis and peroxidases in the BT cultivars. Terpenoids biosynthesis-related enzymes were higher in the OT cultivars. Abstract: Different tea cultivars differ in their manufacturing suitability. In this study, metabolomics and proteomics were applied to investigate the metabolite and protein differences in fresh leaves from 23 Chinese tea cultivars suitable for manufacturing green, white, oolong, and black teas. The combined analysis revealed 115 differential metabolites and significant differences in the biosynthesis pathways for amino acids, phenylpropanoids, flavonoids, and terpenoids, and in the peroxidases abundances among these four groups. Green tea cultivars had higher abundances of amino acids and amino acids biosynthesis-related enzymes but lower abundances of flavanols and flavonoids biosynthesis-related enzymes. Black tea cultivars presented higher abundances of flavanols, flavanol-O-glycosides, flavonoids biosynthesis-related enzymes, and peroxidases. Oolong tea cultivars showed higher abundances of enzymes involved in terpenoids biosynthesis. Our study provides a novel interpretation of the manufacturing suitability of tea cultivars from the perspective of both metabolites and proteins and will be helpful for cultivar breeding.